Capability of geomagnetic storm parameters to identify severe space weather - Balan, N.; Zhang, Qinghe; Xing, Zanyang; Skoug, R.; Shiokawa, Kazuo; Lühr, Hermann; Tulasiram, S.; Otsuka, Yuichi; Zhao, Lingxin (My University, 2019)
The paper investigates the capability of geomagnetic storm parameters in the disturbance storm-time (Dst), Kp, and AE indices to distinguish between severe space weather (SvSW) that causes the reported electric power outages and/or telecommunication failures and normal space weather (NSW) that does not cause these severe effects in a 50 yr period (1958–2007). The parameters include the storm intensities DstMin (minimum Dst during the main phase, MP, of the storm), (dDst/dt)MPmax, Kpmax, and AEmax. In addition, the impulsive parameter IpsDst 1 Dst = -( )∣∣ T dt MP òTMP MP is derived for the storms that are automatically identified in the Kyoto Dst and USGS Dst. Dst ò ∣ ∣dt TMP MP is the integral of the modulus of the Dst from onset of the MP (MPO) to the DstMin. TMP is the MP duration from MPO to DstMin. The corresponding mean values áKpMPñ and áAEMPñ are also calculated. Regardless of the significant differences in the storm parameters between the two Dst indices, the IpsDst in both indices seems to identify four of the five SvSW events (and the Carrington event) in more than 750 NSW events that have been reported to have occurred in 1958–2007, while all other parameters separate one or two SvSWs from the NSWs. Using the Kyoto IpsDst threshold of −250 nT, we demonstrate a 100% true SvSW identification rate with only one false NSW. Using the false NSW event (1972 August 4), we investigate whether using a higher resolution Dst might result in a more accurate identification of SvSWs. The mechanism of the impulsive action leading to large IpsDst and SvSW involves the coincidence that the fast interplanetary coronal mass ejection velocity V contains its shock (or front) velocity V and large interplanetary magnetic field Bz southward covering V.
Keywords: Geomagnetic field; Solar wind; Space weather